Cover & TOC - IJLFS, admin (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 11 No 1 (2021): Indonesian Journal of Legal and Forensic Sciences, 2021)
Indonesian Journal of Legal and Forensic Sciences